Divergent Effects of Metformin on an Inflammatory Model of Parkinson’s Disease - Tayara, Khadija; Espinosa-Oliva, Ana M.; García-Domínguez, Irene; Ismaiel, Afrah Abdul; Boza-Serrano, Antonio; Deierborg, Tomas; Machado, Alberto; Herrera, Antonio J.; Venero, José L.; de Pablos, Rocío M. (Frontiers in Cellular Neuroscience, 2018)
Metformin is a widely used oral antidiabetic drug with known anti-inflammatory properties due to its action on AMP kinase. This drug has shown a protective effect on various brain tissues, including cortical neurons. However, the effect of metformin on the substantia nigra (SN), the main structure affected in Parkinson’s disease (PD), has not yet been studied. Accumulating evidence suggest that inflammation may play a central role in the cell loss that occurs in PD. The aim of this work was to determine the effect of metformin on the microglial activation of the SN of rats using the animal model of PD based on the injection of the pro-inflammogen lipopolysaccharide (LPS). In vivo and in vitro experiments were used to study the activation of microglia at both the cellular and molecular levels. Our results indicate that metformin overall inhibits microglia activation measured by OX-6 (MHCII marker), IKKβ (pro-inflammatory marker) and arginase (anti-inflammatory marker) immunoreactivity. In addition, qPCR experiments reveal that metformin treatment minimizes the expression levels of several pro- and anti-inflammatory cytokines. Furthermore, the drug decreases the phosphorylated forms of MAPKs as well as ROS generation through the inhibition of the NADPH oxidase enzyme. However, metformin treatment fails to protect the dopaminergic neurons of SN. These findings suggest that metformin could have both beneficial and harmful pharmacological effects and arise the question about the potential use of metformin for the prevention and treatment of PD.